Pengaruh Pandemi Covid-19 Terhadap Ekspor-Impor Komoditas Pertanian Indonesia-China - Syeti Agria Ningrum; Vidia Sava Deviani (FISIP Universitas Tanjungpura, 2022)
This paper aims to discuss the impact of the Covid-19 pandemic on the export-import of Indonesian-China agricultural commodities. Indonesia-China relations on export-import activities of agricultural commodities are said to be potential and stable. Until the beginning of 2020, the Covid-19 virus shook the world, followed by regulation of restrictions for each country, which made export-import activities both hampered. The inhibition of export-import of agricultural commodities affects the food security of Indonesia-China. If this condition continues, a food crisis could occur and signify the failure of the government concerned in achieving the targets of the Sustainable Development Goals (SDGs). This paper explains how the impact of Covid-19 on exports and imports of Indonesian-China agricultural commodities and the policies of the two countries in dealing with this influence. The author uses the theory of liberalism. The technique used is document study and literature search or by using literature study. Document study and literature search is a data collection tool through written data. The results of this paper show that the Covid-19 pandemic has had an effect on a sharp decline in the trade balance of agricultural commodities of the two countries, which is an urgency to issue stimulus policies to restore their delayed export-import activities.